Fasting plasma adropin concentrations correlate with fat consumption in human females. (17th October 2013) - St‐Onge, Marie‐Pierre; Shechter, Ari; Shlisky, Julie; Tam, Charmaine S.; Gao, Su; Ravussin, Eric; Butler, Andrew A.
<x xml:space="preserve">Abstract</x> Objective This study investigated whether plasma adropin concentrations are influenced by sleep restriction and correlate with dietary preferences. Methods Plasma adropin concentrations were measured by ELISA using samples from a study that investigated feeding behavior in sleep deprived lean (body mass index 22‐26 kg/m2) men and women aged 30‐45 y. Sleep (habitual or restricted to 4h/night) and diet were controlled during a 4‐day inpatient period. On day 5, food was self‐selected (FS). Adropin was measured on day 4 in samples collected throughout the day, and then after an overnight fast at 0730 on days 5 (Pre‐FS) and 6 (Post‐FS). Results Plasma adropin concentrations were not affected by sleep restriction. However, circulating adropin concentrations correlated with food selection preferences in women, irrespective of sleep status. Pre‐FS adropin correlated positively with fat intake (total fat, r = 0.867, P < 0.05; saturated fat, r = 0.959, P < 0.01) and negatively with carbohydrate intake (r = ‐0.894, P < 0.05) as a percent total energy. Post‐FS adropin correlated with total (r = 0.797, P < 0.05) and saturated fat intake (r = 0.945, P < 0.01), and negative with total carbohydrate intake (r = ‐0.929, P < 0.01). Pre‐FS adropin also correlated with fat intake in kcal adjusted for body size (total fat, r = 0.852, P < 0.05; saturated fat, r = 0.927, P < 0.01). Conclusions Plasma adropin concentrations correlate with fat consumption in women.